2012
DOI: 10.1126/science.1218713
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Human Enterovirus 71

Abstract: Enterovirus 71 is a picornavirus associated with fatal neurological illness in infants and young children. Here we report the crystal structure of enterovirus 71 and show that, unlike in other enteroviruses, the “pocket factor”, a small molecule that stabilizes the virus, is partly exposed on the floor of the canyon. Thus the structure of antiviral compounds may require a hydrophilic head group designed to interact with residues at the entrance of the pocket.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
170
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(179 citation statements)
references
References 15 publications
4
170
0
Order By: Relevance
“…The structures of different strains of EV71 have been determined (20)(21)(22). By comparing the structures of the mature virion and a naturally occurring empty particle (sedimentation coefficient of 80S), Wang et al proposed a sensor-adaptor mechanism for EV71 uncoating (21) and found that the largest movement of the polypeptide occurs in residues 230 to 233 of VP1 at the end of the GH loop and at the beginning of strand H. They referred to this polypeptide region as the adaptor-sensor, which is directly downstream of a region of the GH loop that is external and structurally variable in poliovirus (21).…”
mentioning
confidence: 99%
“…The structures of different strains of EV71 have been determined (20)(21)(22). By comparing the structures of the mature virion and a naturally occurring empty particle (sedimentation coefficient of 80S), Wang et al proposed a sensor-adaptor mechanism for EV71 uncoating (21) and found that the largest movement of the polypeptide occurs in residues 230 to 233 of VP1 at the end of the GH loop and at the beginning of strand H. They referred to this polypeptide region as the adaptor-sensor, which is directly downstream of a region of the GH loop that is external and structurally variable in poliovirus (21).…”
mentioning
confidence: 99%
“…There is a circular depression or "canyon" around each icosahedral fivefold axis of symmetry on the surface of many picornaviruses (3,4). The EV71 canyon is shallower than that in polioviruses and rhinoviruses (5,6).…”
mentioning
confidence: 99%
“…Recently, we and others have reported the structures of the virion, the naturally occurring empty particle, an uncoating intermediate or the A-particle, and the empty particle after the uncoating of EV71 as determined by x-ray crystallography or cryo-EM techniques (17)(18)(19)(20)(21). Despite its elusive role during the viral life cycle, the empty particle shares similar structural features with the virion and the uncoating intermediate.…”
mentioning
confidence: 99%